The Effectiveness of Using Inside Outside Circle Technique towards Students’ Speaking Ability at Tenth Grade Student of Senior High School 8 Muaro Jambi - Ismiyati, Yanti; Dinata, Ridho Praja; Meldyasativa, Zeriska Putri (Universitas Batanghari Jambi, 2023)
This study aims to investigate the effectiveness of using Inside Outside Circle Technique Towards Speaking Skill at Eleventh Grade student of Senior High School 8 Muaro Jambi. The research methodology used in this study was quantitative research design with true experimental research. The population of the research was eleventh grade student and the sample was XI IPA 2 as experimental class and XI IPA 3 as control class. The instrument of the research was the oral proficiency test. The data were gathering in this research through pre-test, treatment and post-test. The data were analyzing in this research through t-test formula. As expected, the current study, it was found that the coefficient of t-(observation) = 4,05 where the coefficient of t-(table) = 1,967. It means that there is a significant effect of using Inside Outside Circle technique toward students English speaking skill at eleventh grade student of senior high school 8 Muaro Jambi.